Condensation of long-term wave climates for the fatigue design of hydrodynamically sensitive offshore wind turbine support structures. (17th February 2016) - Passon, Patrik; Branner, Kim
Abstract : Cost-efficient and reliable fatigue designs of offshore wind turbine support structures require an adequate representation of the site-specific wind–wave joint distribution. Establishment of this wind–wave joint distribution for design load calculation purposes requires typically a correlation of the marginal wind and wave distribution. This is achieved by condensation of the site-specific wave climate in terms of wave period or wave height lumping, subsequently used as input for a correlation with the corresponding wind climate. The quality of this resulting wind–wave correlation is especially important for hydrodynamically sensitive structures since the applied met-ocean parameters have a non-linear influence on calculated fatigue design loads. The present article introduces a new wave lumping method for condensation of the wave climate. The novelty is predominantly based on refined equivalence criterions for fatigue loads aiming at preservation of the fatigue damage distribution over either the wave height or wave period distribution. This new method is assessed in comparison with different other traditional wave lumping methods on the basis of the site-specific wave climate for the offshore wind farm project Gemini which has kindly been made available by the developer Typhoon Offshore. It is shown that the new method allows for a significantly better preservation of the hydrodynamic fatigue in comparison to the traditional methods.